An Investigation of Student Participation in Collaborative Problem Solving in Mathematics: Positioning and Negotiation among Four Chinese Students - Shu Zhang; Man Ching Esther Chan; David Clarke; Yiming Cao (Korea Society of Educational Studies in Mathematics, 2021)
In this paper we report on a case study involving four Chinese students; the aim of the study was to develop a conceptual framework for investigating student participation in a collaborative task in mathematics. Building on previous research on student participation, we defined student participation in a collaborative task in mathematics as the process of taking part in student interactions and task completions. A video recording and transcript of students involved with collaborative task in mathematics were analyzed. Four categories (initiation, response, evaluation, and non-interactive) were created for analyzing the students' interactions. The four students showed different approaches to communicating with other group members. The content of the group's discussion was examined in terms of the negotiation process. By looking at the content of the group's discussion, the process how the group work on the task could be revealed. We identified that students showed involvement in the group discussion by proposing and revisiting topics. It was found that through forming an interactive pair, students might be able to take up the leading role in working on the task and controlling the conversation of the group.